2011
DOI: 10.1007/s11540-011-9198-x
|View full text |Cite
|
Sign up to set email alerts
|

Salt and Drought Stress Tolerances in Transgenic Potatoes and Wild Species

Abstract: Transgenic potatoes were employed to test whether a diverse range of gene actions can induce different stress tolerance(s). To select available transgenic lines, we measured growth profiles under non-stress conditions in our evaluation of transgenic lines and confirmed productivity under stress(es). We performed microarray analyses to clarify the abiotic stress tolerance mechanism controlled by AtDREB1A. Two transgenic lines out of over 200 independent genotypes displayed stable tuber production under high sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…() found no consistent trend of drought tolerance among cultivated and wild plants, while Nevo and Chen () found a greater drought resistance in wild wheat and barley than cultivated counterparts. By contrast, some others suggested that drought tolerant‐targeted transgenetic cultivated plants had strong resistance to drought than even wild plants (Fita, Rodriguezburruezo, Boscaiu, Prohens, & Vicente, ; Seversike, ; ,b; Watanabe, Kikuchi, Shimazaki, & Asahina, ). Taken together, these comparisons suggested that drought tolerance of crops and wild plants may be species‐specific.…”
Section: Discussionmentioning
confidence: 99%
“…() found no consistent trend of drought tolerance among cultivated and wild plants, while Nevo and Chen () found a greater drought resistance in wild wheat and barley than cultivated counterparts. By contrast, some others suggested that drought tolerant‐targeted transgenetic cultivated plants had strong resistance to drought than even wild plants (Fita, Rodriguezburruezo, Boscaiu, Prohens, & Vicente, ; Seversike, ; ,b; Watanabe, Kikuchi, Shimazaki, & Asahina, ). Taken together, these comparisons suggested that drought tolerance of crops and wild plants may be species‐specific.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of potato plants to tolerate drought stress is believed to be governed by upregulation DREB1A (Dehydrin responsive element binding protein) regulons (Schafleitner et al, 2007). To support this, Watanabe et al (2011) compared AtDREB1a transgenic potato with non-transgenic ones and observed increased drought tolerance in DREB1a transgenic lines. Transgenic potato plants overexpressing ScCBFI gene from Solanum commersonii exhibit increased drought tolerance as indicated by improved overall plant performance and extensive root development following drought stress (Pino et al, 2013).…”
Section: Drought Adaptation Strategiesmentioning
confidence: 97%
“…Studies show that the dehydrins interact with membranes in the interior of cells and reduce dehydration induced damage through their ability to replace water and, through their hydroxyl groups (Baker et al, 1995 ) and dehydrins are shown to play a fundamental role in plant response and adaptation to abiotic stress (Hanin et al, 2011 ). Comparing expression analysis in non-transgenic potato and AtDREB1A (Dehydrin responsive element binding protein) transgenic potato suggest that potato may have mechanisms in abiotic stress tolerance controlled by native TFs similar to AtDREB1A (Watanabe et al, 2011 ). The over expression of StMYB1R-1 (MYB-like transcription factor) improved plant tolerance to stress and it is thought that the induced upregulated expression of AtHB-7 (Arabidopsis homeobox gene), RD28 (Responsive to desiccation), ALDH (Aldehyde dehydrogenase), and ERD15 (Early response to dehydration) under drought stress conditions enhances tolerance (Shin et al, 2011 ).…”
Section: Drought Effects On Potatomentioning
confidence: 99%